Japanese at Work Politeness, Power, and Personae in Japanese Workplace Discourse - Cook, Haruko Minegishi; Shibamoto-Smith, Janet S. (Communicating in Professions and Organizations, 2018)
IX, 234 p. 1 illus. in color.